Eight Years of Research Related to the Green Sukuk in the Global Stock Exchange Market to Support the Implementation of SDG: A Bibliometric Review - Nanang Qosim; Ririn Tri Ratnasari; Akhmad Kusuma Wardhana; Hasna Fauziana; Tiara Tresnawulan Barkah (Journal of Islamic Economic and Business Research, 2023)
The awareness of investors that only invest in green instruments has been increasing recently. Green sukuk was an investment that followed the Sharia principle and promoted environmental preservation. This study aims to analyze green sukuk in previous studies as an alternative financing for green infrastructure development in Indonesia. This study used a bibliometric method by taking secondary data from meta-data papers from Scopus and SCI. Forty papers from Scopus and 29 from SCI during 2016-2023 were taken as samples. Data were analyzed with Vosviewer and Biblioshiny. The results of this study show that the energy was closely related to the topic of green sukuk. Energy was mostly used in the abstract and titles of papers. Moreover, the abstract and the title showed that the word sustainable was used frequently, implying that the energy power plant could become an underlying asset for green sukuk due to its sustainable revenue. However, the government should take action to create regulations that could support the green project as an underlying asset of Green Sukuk.